Comparison of vertical breast displacement between two different sports bra designs - Parunchaya Jamkrajang; Weerawat Lımroongreungrat (Türk Spor ve Egzersiz Dergisi)
Breast pain during exercise could come from the strain on the breast due to large repetitive breast motion. Proper sports bra should provide not only a support but also reduce breast movement. Since movement in each sport is different, several sport bras are presently designed for each particular sport motion such as walking, jogging and running. However, breast displacement of these sport bra designs has not been investigated particularly in Thailand. The purpose of this study was to compare vertical breast displacement between 3 conditions: no bra (NB), compression bra (CB) and encapsulation (EB). Thirty female collegiate athletes (meanage = 22.33 + 2.7 yrs, meanwt 57.3 + 5.9 Kg, BMI= 20.9±1.4) cup size B75 – C70 were volunteered in the study. All subjects were required to walk (3 km/hr), jog (6 km/hr) and run (9 km/hr) on the treadmill for 5 minutes under 3 bra conditions. The order of both bra conditions and activities were randomly assigned. Four retro reflective markers were placed on both nipples and on clavicles directly above nipple lines. Eight 100-Hz cameras were used to collect kinematic data. The results showed that no statistically significant differences of vertical breast displacement during walking and jogging between two types of sports bra. However, vertical breast displacement of EB during running was significantly greater than CB. Nevertheless, the displacement between the left and right sides was slightly different on EB while CB was almost symmetrical. In conclusion, CB provides greater support and reduction of vertical breast displacement. However, this design does not provide breast motion independently.